The Effect of Self-Efficacy and Competence on Service Quality with Organizational Culture as a Moderating Variable PT. Bank Rakyat Indonesia Makassar Somba Opu Branch - Rizky Yuliasari; Maat Pono; Wahda Wahda (Jurnal Mirai Management, 2023)
This study aims to determine the effect of self-efficacy and competence on service quality with organizational culture as a moderating variable. This type of research is quantitative with a descriptive approach. The population of this research is all employees at PT. Bank Rakyat Indonesia Makassar Somba Opu Branch has 100 employees. Determination of the sample using the total sampling method in which the entire population is used as a sample. So that the sample of this study is 100. The hypothesis testing in this study uses the SmartPLS 3 application. The results of this study indicate that self-efficacy has a positive and significant effect on service quality, competence has a positive and significant effect on service quality, organizational culture is unable to moderate the influence between self-efficacy on service quality, and organizational culture strengthens the influence of competence on service quality. Keywords: self-efficacy, competence, organizational culture, service quality.